Dataset of cocoa aspartic protease cleavage sites - Katharina Janek; Agathe Niewienda; Johannes Wöstemeyer; Jürgen Voigt (Data in Brief, 2016)
The data provide information in support of the research article, “The cleavage specificity of the aspartic protease of cocoa beans involved in the generation of the cocoa-specific aroma precursors” (Janek et al., 2016) [1]. Three different protein substrates were partially digested with the aspartic protease isolated from cocoa beans and commercial pepsin, respectively. The obtained peptide fragments were analyzed by matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/TOF-MS/MS) and identified using the MASCOT server. The N- and C-terminal ends of the peptide fragments were used to identify the corresponding in-vitro cleavage sites by comparison with the amino acid sequences of the substrate proteins. The same procedure was applied to identify the cleavage sites used by the cocoa aspartic protease during cocoa fermentation starting from the published amino acid sequences of oligopeptides isolated from fermented cocoa beans. Keywords: Aspartic protease, Cleavage sites, Cocoa, In-vitro proteolysis, Mass spectrometry, Peptides